2011
DOI: 10.1039/c0mb00234h
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and characterization of the biosynthetic gene cluster of sanglifehrin A, a potent cyclophilin inhibitor

Abstract: Sanglifehrin A (SFA), a potent cyclophilin inhibitor produced by Streptomyces flaveolus DSM 9954, bears a unique [5.5] spirolactam moiety conjugated with a 22-membered, highly functionalized macrolide through a linear carbon chain. SFA displays a diverse range of biological activities and offers significant therapeutic potential. However, the structural complexity of SFA poses a tremendous challenge for new analogue development via chemical synthesis. Based on a rational prediction of its biosynthetic origin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 41 publications
3
68
0
4
Order By: Relevance
“…We constructed DpadO and its complemented mutant (Figure 2A; Figure S2C), and the HPLC results showed that the DpadO mutant abolished padanamide production, indicating that it probably acts as a pathway activator. PadO also has sequence identity of 51% to Orf4 of the kutzneride gene cluster (Fujimori et al, 2007) and 45% to SfaC of the sanglifehrin gene cluster (Qu et al, 2011). Both Orf4 and SfaC are annotated as putative regulators; however, no genetic evidence is available.…”
Section: Additional Precursor Biosynthesis and Regulationmentioning
confidence: 97%
See 2 more Smart Citations
“…We constructed DpadO and its complemented mutant (Figure 2A; Figure S2C), and the HPLC results showed that the DpadO mutant abolished padanamide production, indicating that it probably acts as a pathway activator. PadO also has sequence identity of 51% to Orf4 of the kutzneride gene cluster (Fujimori et al, 2007) and 45% to SfaC of the sanglifehrin gene cluster (Qu et al, 2011). Both Orf4 and SfaC are annotated as putative regulators; however, no genetic evidence is available.…”
Section: Additional Precursor Biosynthesis and Regulationmentioning
confidence: 97%
“…Accessory genes would be involved in the construction of the 2-methoxyacetyl group and might resemble the starter unit pathway for apoptolidins (Du et al, 2011). Additionally, an ornithine N-monooxygenase would likely generate N 5 -OH-ornithine, the precursor to Piz, as observed in the biosynthesis of the kutznerides (Fujimori et al, 2007), sanglifehrin A (Qu et al, 2011), himastatin (Ma et al, 2011), and other Piz-containing natural products. To find the padanamide gene cluster, we initially explored isolation of adenylation (A) domain and N-oxygenase genes from RJA2928 genomic DNA using PCR with degenerate primers.…”
Section: Identification Of the Padanamide Biosynthetic Gene Clustermentioning
confidence: 97%
See 1 more Smart Citation
“…Rapamycine, die Verbindungen der FK506-Familie, [7,8] Sanglifehrin [9] und die Epothilone sind Beispiele für therapeutisch interessante Gruppen solcher molekularer NRP-PKHybride mit nichtproteinogenen Aminosäureeinheiten. [10,11] 2.…”
Section: Introductionunclassified
“…Samples were determined to be methylated or unmethylated on the basis of the visible peaks generated by the Q-Analyzer. The methylated and unmethylated primer sequences of CDKN2B (27), SLC19A3 (28) and DLEC1 (29) genes are presented in Table II . Some of the DNA samples were sequenced using an ABI 3730 DNA Analyzer (Applied Biosystems; Thermo Fisher Scientific, Inc.), and the results indicated a successful bisulfite conversion and amplification (Fig.…”
Section: Methylation-specific Polymerase Chain Reaction (Msp)mentioning
confidence: 99%